Manufacturing method of low-alloy ferrite steel CT sample precrack
By adopting the pull-pull fatigue method and the four-stage load reduction strategy, the problems of low pre-crack production efficiency and low pass rate of CT samples of low alloy ferrite steel are solved, and efficient and low-cost pre-crack production is achieved, meeting the requirements of the ASTM E1921 standard.
Patent Information
- Application Number
- CN202510319305.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-06-03
AI Technical Summary
The production efficiency of pre-cracks of low alloy ferrite steel CT samples is low, the pass rate is low, and the cost is high, making it difficult to meet the complex requirements of the ASTM E1921 standard.
The pre-crack is produced by pull-pull fatigue method. By calculating the allowable load, it is divided into four stages to reduce the load step by step to ensure that the stress intensity factor is within the envelope range, and image acquisition and nine-point measurement are used to realize the process-based, data-based and visual production process.
It improves sample preparation efficiency and pass rate, reduces the use of precious nuclear power raw materials, reduces costs, and ensures that pre-cracks meet the standard requirements.
Smart Images

Figure CN120084616A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of CT specimen preparation, and more particularly to a method for making a pre-crack in a CT specimen of low alloy ferritic steel. Background Art
[0002] The RPV is one of the most critical components in a pressurized water reactor nuclear power plant. It confines the chain reaction within a closed space and operates under high temperature, high pressure, and strong irradiation environments for a long time. It is a large-scale equipment that cannot be replaced during the entire life cycle of the nuclear power plant. Therefore, its structural integrity directly determines the safe operation of the reactor. During the operation of the reactor, the performance of the RPV will gradually decline due to multiple reasons, and fast neutron irradiation embrittlement is the most important factor. Irradiation embrittlement will lead to a decrease in the toughness of the material and an increase in the ductile-brittle transition temperature, which may induce brittle failure and cause catastrophic consequences. Therefore, it is necessary to detect the performance of the RPV material.
[0003] To monitor the irradiation embrittlement of the RPV, the general practice is to place an irradiation surveillance tube in the RPV, take it out of the reactor, and measure the performance of the material after irradiation to ensure the structural integrity and reliability of the RPV. The mechanical property test samples in the irradiation surveillance tube generally include tensile specimens, impact specimens, bending specimens, and CT specimens. The CT specimens loaded in the irradiation surveillance tube are used to test the fracture toughness of the material, specifically 0.5T-CT specimens with a thickness of 12.7 mm.
[0004] In the manufacturing process of CT specimens, a fatigue method is required to make pre-cracks at the crack tips. Low alloy ferritic steel (RPV steel) has good toughness, and the ASTM E1921 Standard Test Method for Determination of Reference Temperature, To, for Ferritic Steels in the Transition Range has very clear and complex requirements for the final results of pre-crack production. Therefore, the sample preparation efficiency is poor, the qualification rate is low, and the cost is high. Therefore, how to develop and streamline the pre-crack production technology for CT specimens of low alloy ferritic steel (RPV steel) and establish a streamlined pre-crack production method is an urgent problem to be solved at present.
[0005] In view of this, the present application is specifically proposed. Summary of the Invention
[0006] To solve the above technical problems, the present invention provides a method for making a pre-crack in a CT specimen of low alloy ferritic steel, which can make the pre-crack meet the requirements for pre-crack production in the standard, streamline, digitalize, and visualize the pre-crack production process, improve the sample preparation efficiency and the qualification rate of sample preparation, reduce the consumption of precious nuclear power raw materials, and lower the cost.
[0007] The present invention is realized by the following technical solutions:
[0008] In a first aspect, the present invention provides a method for fabricating a pre-crack in a CT specimen of low-alloy ferritic steel, which is fabricated by a tension-tension fatigue method and includes the following steps:
[0009] S1. Calculate the allowable load for pre-crack fabrication according to the stress intensity factor requirements during fatigue.
[0010] S2. Draw multiple parallel lines with a specific spacing at specific positions on the upper, lower, front, and back sides of the CT specimen.
[0011] S3. Install the CT specimen at the test position of the testing machine.
[0012] S4. Arrange 2 image acquisition cameras and a light source. The cameras are focused on the crack front positions on both the front and back sides of the specimen. Obtain images through the display. Adopt the tension-tension fatigue method according to the preset load, and gradually fabricate the pre-crack through four stages. Observe, measure, and record the length of the pre-crack propagation in-situ online until the preset pre-crack length is reached.
[0013] The low-alloy ferritic steel (RPV steel) mentioned refers to a typical nuclear reactor pressure vessel steel, and this material has good toughness.
[0014] The CT (Compact Tension) specimen, also known as the compact tension specimen. This specimen has standard external dimension ratios and tolerance requirements, as detailed in the ASTM E1921 Standard Test Method for Determination of Reference Temperature, To, for Ferritic Steels in the Transition Range standard.
[0015] The pre-crack is a part of the complete CT specimen. It is a through crack existing on the specimen. The pre-crack needs to be fabricated by a fatigue method using a material mechanics testing machine with a fatigue function.
[0016] During the manufacturing process of CT specimens, a fatigue method is required to create a pre-crack at the crack tip. Low-alloy ferritic steel (RPV steel) has good toughness, and the ASTM E1921 Standard Test Method for Determination of Reference Temperature, To, for Ferritic Steels in the Transition Range has very clear and complex requirements for the final result of pre-crack manufacturing. Therefore, the sample preparation efficiency is poor and the qualified rate is low.
[0017] The present invention can make the pre-crack meet the requirements for pre-crack manufacturing in the standard, streamline, digitalize, and visualize the pre-crack manufacturing process, improve the sample preparation efficiency and the qualified rate of sample preparation, reduce the consumption of precious nuclear power raw materials, and lower the cost.
[0018] In a specific embodiment, the pre-crack manufacturing needs to be carried out in the upper platform temperature region of the impact energy of the RPV material, generally at room temperature.
[0019] In a specific embodiment, in the step S1, the allowable load includes four stages, and the loads of the four stages decrease gradually and the load of each stage is constant.
[0020] The stress intensity factor during the fatigue process needs to meet certain requirements to ensure that the stress intensity factor is within the envelope range, that is, the stress intensity factor K in the initial propagation stage should be less than 25 MPam 0.5 , △a f The stress intensity factor in the stage should be less than 15 MPam 0.5 , △a sh The stress intensity factor in the stage should be between the above two. Therefore, in order to meet the stress intensity factor requirements during the fatigue process, it is necessary to calculate and limit the load of the fatigue method.
[0021] In a specific embodiment, the load ranges of the four stages are specifically as follows:
[0022] In the first stage, the load range is 4.8 - 5.2 kN, and the preferred load is 5 kN;
[0023] In the second stage, the load range is 3.8 - 4.2 kN, and the preferred load is 4 kN;
[0024] In the third stage, the load range is 3.4 - 3.6 kN, and the preferred load is 3.5 kN;
[0025] In the fourth stage, the load range is 2.8 - 3.2 kN, and the preferred load is 3 kN.
[0026] Among them, the load range of each stage represents the preferred load selection applied, and it does not mean that the load slightly exceeding the load range cannot achieve the above invention. For the CT specimens of low-alloy ferritic steel with different compositions, the above range may have a slight fluctuation according to the hardness of the material, etc. The load range listed above is based on the load range that satisfies the production of most low-alloy ferritic steel CT specimens.
[0027] The present invention divides the applied load into four stages. According to four preset and gradually decreasing constant loads, the pre-crack is made by the tension-tension fatigue method. When the preset pre-crack length is reached in each stage, the load level of the next stage is switched until the pre-crack required by the specimen is reached.
[0028] In a specific embodiment, the relationship between the stress intensity factor K and the load P is as follows:
[0029]
[0030] In the formula, B is the specimen thickness, W is the specimen width, and a 0 is the initial crack length.
[0031] In the first stage, a 0 represents the initial crack length, that is, the length of the notch pre-machined on the specimen mechanically before the fatigue experiment;
[0032] In the second stage, a 0 represents the sum of the initial crack length and the pre-crack length after expansion in the first stage;
[0033] In the third stage, a 0 represents the sum of the initial crack length and the pre-crack length after expansion in the second stage;
[0034] In the fourth stage, a 0 represents the sum of the initial crack length and the pre-crack length after expansion in the third stage.
[0035] In a specific embodiment, the stress intensity factor ranges of the four stages are specifically as follows:
[0036] In the first stage, the stress intensity factor range is 19 - 22 MPam 0.5 ;
[0037] In the second stage, the stress intensity factor range is 18 - 19 MPam 0.5 ;
[0038] In the third stage, the stress intensity factor range is 14 - 15 MPam 0.5 ;
[0039] In the fourth stage, the stress intensity factor range is 13 - 14 MPam0.5 。
[0040] In each stage, the load is constant while the stress intensity factor increases linearly within the above range.
[0041] The stress intensity factor ranges for each of the above stages are similar to the aforementioned load ranges. For CT specimens of low-alloy ferritic steel with different compositions, these ranges may vary slightly depending on material hardness, etc. The ranges listed above are based on those that satisfy the fabrication of the vast majority of low-alloy ferritic steel CT specimens.
[0042] In a specific embodiment, in step S4, the nine-point method is used to measure the pre-crack propagation length, and the method is as follows:
[0043] Along the direction of the specimen thickness B, the lengths a' are read at positions 0.01B from the upper and lower surfaces of the specimen respectively 1 、a' 9 , and the lengths a' are taken at equal intervals of 0.01B between the upper and lower surfaces of the specimen 2 、a' 3 、a' 4 、a' 5 、a' 6 、a' 7 、a' 8 , and the pre-crack length Δa is calculated:
[0044]
[0045] The present invention establishes the relationship between the crack propagation length of the specimen and the measurement of the crack propagation length by the nine-point method, so as to improve the accuracy of measuring the crack propagation length of the specimen during the pre-crack fabrication process.
[0046] However, during the actual pre-crack fabrication process, generally only the crack propagation conditions on the upper and lower front and back surfaces of the specimen can be observed, and the pre-crack propagation amount at the center position of the specimen cannot be determined. Therefore, only the pre-crack length of the entire specimen can be extrapolated based on the crack propagation conditions on the surface of the specimen. Through the fitting empirical formula of the present invention, the pre-crack length of the entire specimen can be estimated using the crack lengths on the front and back surfaces of the specimen.
[0047] In the present invention, the pre-crack length Δa is based on the pre-crack lengths f1 and f2 on the front and back surfaces of the specimen, and there is a direct relationship between the arc shape of the crack front and the specimen thickness B. According to a large amount of existing similar data, the corresponding relationship between the pre-crack length Δa and the mean of the pre-crack lengths on the two surfaces of the specimen (f1 + f2) / 2 and the specimen thickness B is fitted as follows.
[0048] Δa = (f 1 + f 2 ) / 2 + 0.0466B
[0049] According to the above formula, only by measuring the thickness B of the specimen and the crack propagation lengths f1 and f2 on the specimen surface can the pre-crack length be estimated relatively accurately, so that it can be applied to the rapid evaluation of the pre-crack length during the test process. The above formula is an empirical formula formulated by the present invention based on several experimental results and is used for the rapid and accurate evaluation of the pre-crack length.
[0050] In a specific embodiment, in the four stages, the preset pre-crack lengths are as follows:
[0051] In the first stage, the sum of the initial crack length and the preset pre-crack length is 10.7 - 11.6 mm;
[0052] In the second stage, the sum of the initial crack length and the preset pre-crack length is 11.6 - 12.1 mm;
[0053] In the third stage, the sum of the initial crack length and the preset pre-crack length is 12.1 - 12.4 mm;
[0054] In the fourth stage, the sum of the initial crack length and the preset pre-crack length is 12.4 - 12.7 mm.
[0055] In the four stages, corresponding loads are applied in each stage in sequence, and then the pre-crack length is measured. When the length reaches the length pre-designed for each stage, the load can be applied in the next stage.
[0056] The range of the pre-crack length in each of the above stages is similar to the aforementioned load range. For CT specimens of low-alloy ferritic steel with different compositions, the above range may have a small fluctuation according to the hardness of the material, etc. The ranges listed above are based on the ranges that satisfy the production of most low-alloy ferritic steel CT specimens.
[0057] In a specific embodiment, the extended length Δa of the preset pre-crack should be greater than 1.3 mm. The pre-crack lengths on the front and back surfaces of the specimen need to be between 1.5 mm and 1.7 mm, and the difference in the pre-crack lengths between the two surfaces is not greater than 0.1 mm.
[0058] In a specific embodiment, when the pre-cracks in the 4 stages are all completed, the specimen is taken down and placed under a tool microscope for final pre-crack length measurement and image acquisition to determine the final pre-crack quality.
[0059] In a specific embodiment, the CT specimen is a 0.5T-CT specimen of low-alloy ferritic steel.
[0060] In a specific embodiment, the method for making the pre-crack of the CT specimen is as follows:
[0061] (1) First, according to the basic information such as the size of the specimen and the mechanical properties of the raw material, calculate the allowable load for pre-crack fabrication according to the requirements of the stress intensity factor envelope in the ASTM E1921 Standard Test Method for Determination of Reference Temperature, To, for Ferritic Steels in the Transition Range standard, and design the pre-crack load levels for four stages.
[0062] (2) Before the test, draw multiple parallel lines with specific spacings at specific positions on both the front and back sides of the specimen. After the specimen is prepared, install the specimen at the test position of the material mechanics testing machine.
[0063] (3) Arrange 2 image acquisition cameras, arrange the light source, focus the cameras on the crack front positions on both the front and back sides of the specimen, obtain images through the monitor, and intercept and save the images through the computer.
[0064] (4) Use the tension-tension fatigue method to fabricate the pre-crack according to four preset and gradually decreasing constant loads. During the process, observe, measure, and record the crack propagation length online and in-situ. After reaching the preset pre-crack length, switch the load level.
[0065] (5) After the pre-cracks in the four stages are completed, remove the specimen and place it under a tool microscope for pre-crack length measurement and image acquisition.
[0066] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0067] 1. A method for fabricating a pre-crack of a low-alloy ferritic steel CT specimen provided by an embodiment of the present invention can make the pre-crack meet the requirements for pre-crack fabrication in the standard, processify, digitalize, and visualize the pre-crack fabrication process, improve the sample preparation efficiency and the sample preparation qualification rate, reduce the consumption of precious nuclear power raw materials, and lower the cost.
[0068] 2. A method for fabricating a pre-crack of a low-alloy ferritic steel CT specimen provided by an embodiment of the present invention uses 4 levels of gradually decreasing loads to ensure that the stress intensity factor is within the envelope range, can observe, measure, and record the pre-crack change situation online and in real-time, improve the sample preparation qualification rate, and ensure the final pre-crack quality. Description of the Drawings
[0069] To more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following will briefly introduce the drawings required for the embodiments. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, without creative efforts, other related drawings can be obtained based on these drawings.
[0070] Figure 1 is the upper envelope of the existing pre-crack stress intensity factor;
[0071] Figure 2 is the pre-crack applied load at each stage provided by the embodiment of the present invention;
[0072] Figure 3 is the stress intensity factor diagram at each stage provided by the embodiment of the present invention;
[0073] Figure 4 is the method for measuring the pre-crack length by the nine-point method provided by the embodiment of the present invention. Detailed Embodiment
[0074] To make the objectives, technical solutions and advantages of the present invention clearer and more understandable, the following will further elaborate on the present invention in combination with embodiments. The illustrative embodiments of the present invention and their descriptions are only used to explain the present invention and are not intended to limit the present invention.
[0075] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is obvious to those of ordinary skill in the art that the present invention does not have to be implemented with these specific details. In other embodiments, well-known materials or methods are not specifically described to avoid obscuring the present invention.
[0076] Throughout the specification, the reference to "one embodiment", "embodiment", "one example" or "example" means that the specific features, structures or characteristics described in connection with that embodiment or example are included in at least one embodiment of the present invention. Thus, the phrases "one embodiment", "embodiment", "one example" or "example" appearing throughout the specification do not necessarily all refer to the same embodiment or example. In addition, the specific features, structures or characteristics can be combined in any suitable combination and / or sub-combination in one or more embodiments or examples. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0077] The "ranges" disclosed in this application are defined in the form of a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The ranges defined in this way can include the end values or not include the end values, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, ranges of 60-110 and 80-120 are also contemplated. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4, and 5 are listed, then the following ranges are all contemplated: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "a-b" represents an abbreviated representation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been fully listed herein, and "0-5" is only an abbreviated representation of these numerical combinations. Additionally, when stating that a certain parameter is an integer ≥2, it is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0078] If there is no special instruction, all steps of this application can be carried out sequentially or randomly, and preferably sequentially. For example, the method includes steps (a) and (b), which means that the method can include steps (a) and (b) carried out sequentially, or can also include steps (b) and (a) carried out sequentially. For example, when it is mentioned that the method may further include step (c), it means that step (c) can be added to the method in any order. For example, the method can include steps (a), (b), and (c), or can also include steps (a), (c), and (b), or can also include steps (c), (a), and (b), etc.
[0079] If there is no special instruction, the "including" and "comprising" mentioned in this application mean open-ended, and can also be closed-ended. For example, the "including" and "comprising" can mean that other components not listed can also be included or comprised, or can only include or comprise the listed components.
[0080] If there is no special instruction, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) while B is true (or exists); or both A and B are true (or exist).
[0081] A significant feature of the CT specimen is that there is a pre-crack made by the fatigue method on the specimen. The so-called pre-crack refers to an artificial through-crack on the specimen that is fine, with a non-passivated tip, and within a specific length range. The number of 0.5T-CT specimens in the domestic pressurized water reactor RPV irradiation surveillance tubes is shown in Table 1 below.
[0082] Table 1
[0083] Model Nuclear power plant to which it belongs Number of CT specimens in each irradiation supervision tube CNP650 Second Phase of Qinshan Nuclear Power Plant A total of 12, 6 for base materials and 6 for welding materials. M310 Daya Bay, Ling'ao A total of 12, 6 for base materials and 6 for welding materials. AP1000 Unit 1 and Unit 2 of Sanmen A total of 24, two groups of base materials, 8 in each group; one group of welding materials, 8 in each group.
[0084] Previously, the irradiation surveillance tubes were all manufactured by foreign companies such as AREVA and WESTING HOUSE. In recent years, the irradiation surveillance tubes have been domesticated and applied to reactor types such as HPR1000. Therefore, the key technologies in production and manufacturing need to be focused on and protected.
[0085] In the manufacturing process of CT specimens, the pre-crack at the crack tip needs to be made by the fatigue method. The low-alloy ferritic steel (RPV steel) has good toughness, and the ASTM E1921 Standard Test Method for Determination of Reference Temperature, To, for Ferritic Steels in the Transition Range has very clear and complex requirements for the final result of pre-crack making. Therefore, the sample preparation efficiency is poor and the qualified rate is low. Therefore, how to develop and solidify the pre-crack making technology for CT specimens of low-alloy ferritic steel (RPV steel) and establish a process-based pre-crack making method is an urgent problem to be solved at present.
[0086] Therefore, to solve the above technical problems:
[0087] The present invention provides a method for making a pre-crack of a low-alloy ferritic steel CT specimen, which is made by the tension-tension fatigue method and includes the following steps:
[0088] S1. Calculate the allowable load for pre-crack making according to the stress intensity factor requirement during fatigue.
[0089] S2. Draw multiple parallel lines with a specific spacing at specific positions on the upper and lower front and back sides of the CT specimen.
[0090] S3. Install the CT specimen at the test position of the material mechanics testing machine.
[0091] S4. Arrange 2 image acquisition cameras, arrange the light source, the cameras focus on the crack front positions on the front and back sides of the specimen, obtain images through the display, and gradually make the pre-crack by the tension-tension fatigue method in four stages according to the preset load, and online in-situ observe, measure, and record the length of pre-crack propagation until the preset pre-crack length is reached.
[0092] The low-alloy ferritic steel (RPV steel) mentioned refers to a typical nuclear reactor pressure vessel steel, and this material has good toughness. The CT (Compact Tension) specimen mentioned, also known as the compact tension specimen. This specimen has standard external dimension ratios and tolerance requirements, for details, see the ASTM E1921 Standard Test Method for Determination of Reference Temperature, To, for Ferritic Steels in the Transition Range standard.
[0093] The pre-crack mentioned is a part of the complete CT specimen. It is a through crack existing on the specimen. The pre-crack needs to be made by using a fatigue method with a material mechanics testing machine with fatigue function.
[0094] The manufacturing method of the present invention can make the pre-crack meet the requirements for the manufacture of pre-cracks in the ASTM E1921 Standard Test Method for Determination of Reference Temperature, To, for Ferritic Steels in the Transition Range standard, and the provided method is simple, process-based, and has a high qualification rate.
[0095] In a specific embodiment, the pre-crack manufacturing needs to be carried out in the upper shelf temperature region of the impact energy of the RPV material, generally at room temperature.
[0096] In a specific embodiment, in the step S1, the allowable load includes four stages, and the loads of the four stages decrease gradually and the load of each stage is constant.
[0097] The present invention adopts a four-stage gradually decreasing load to ensure that the stress intensity factor is within the envelope range, and can observe, measure, and record the change of the pre-crack online in real time, ensuring the final pre-crack quality.
[0098] The stress intensity factor during the fatigue process needs to meet certain requirements to ensure that the stress intensity factor is within the envelope range, that is, the stress intensity factor K in the initial propagation stage should be less than 25 MPam 0.5 , △a f The stress intensity factor in the stage should be less than 15 MPam 0.5 , △a sh The stress intensity factor in the stage should be between the above two. Therefore, in order to meet the requirements of the stress intensity factor during the fatigue process, it is necessary to calculate and limit the load of the fatigue method.
[0099] In a specific embodiment, the load ranges of the four stages are as follows:
[0100] In the first stage, the load range is 4.8 - 5.2 kN, and the preferred load is 5 kN;
[0101] In the second stage, the load range is 3.8 - 4.2 kN, and the preferred load is 4 kN;
[0102] In the third stage, the load range is 3.4 - 3.6 kN, and the preferred load is 3.5 kN;
[0103] In the fourth stage, the load range is 2.8 - 3.2 kN, and the preferred load is 3 kN.
[0104] The present invention divides the applied load into four stages. According to four preset and gradually decreasing constant loads, the pre-crack is fabricated by the tension-tension fatigue method. When the preset pre-crack length is reached in each stage, the load level of the next stage is switched until the pre-crack required for the specimen is achieved.
[0105] In a specific embodiment, the relationship between the stress intensity factor K and the load P is as follows:
[0106]
[0107] In the formula, B is the specimen thickness, W is the specimen width, and a 0 is the initial crack length.
[0108] In the first stage, a 0 represents the initial crack length, that is, the length of the notch pre-machined on the specimen mechanically before the fatigue experiment;
[0109] In the second stage, a 0 represents the sum of the initial crack length and the pre-crack length after extension in the first stage;
[0110] In the third stage, a 0 represents the sum of the initial crack length and the pre-crack length after extension in the second stage;
[0111] In the fourth stage, a 0 represents the sum of the initial crack length and the pre-crack length after extension in the third stage.
[0112] In a specific embodiment, the stress intensity factor ranges of the four stages are as follows:
[0113] In the first stage, the stress intensity factor range is 19 - 22 MPam 0.5 ;
[0114] In the second stage, the stress intensity factor range is 18 - 19 MPam 0.5 ;
[0115] In the third stage, the stress intensity factor range is 14 - 15 MPam 0.5 ;
[0116] In the fourth stage, the stress intensity factor range is 13 - 14 MPam 0.5 .
[0117] In each stage, the load is constant, while the stress intensity factor linearly increases within the above range.
[0118] In a specific embodiment, in step S4, the measurement of the pre - crack propagation length adopts the nine - point method, and the method is as follows:
[0119] Along the direction of the specimen thickness B, the lengths a' 1 , a' 9 are respectively read at positions 0.01B from the upper and lower surfaces of the specimen. At equal intervals of 0.01B between the upper and lower surfaces of the specimen, the lengths a' 2 , a' 3 , a' 4 , a' 5 , a' 6 , a' 7 , a' 8 are taken, and the pre - crack length Δa is calculated:
[0120]
[0121] The present invention establishes the relationship between the crack propagation length of the specimen and the measurement of the crack propagation length by the nine - point method, so as to improve the accuracy of measuring the crack propagation length of the specimen during the pre - crack production process.
[0122] However, during the actual pre - crack production process, generally only the crack propagation conditions on the upper and lower front and back surfaces of the specimen can be observed, and the pre - crack propagation amount at the center position of the specimen cannot be determined. Therefore, only the pre - crack length of the entire specimen can be extrapolated based on the crack propagation conditions on the surface of the specimen. Through the fitted empirical formula, the present invention can estimate the pre - crack length of the entire specimen using the crack lengths on the front and back surfaces of the specimen.
[0123] In the present invention, the pre - crack length △a is based on the pre - crack lengths f1 and f2 on the front and back surfaces of the specimen, and there is a direct relationship between the arc shape of the crack front and the specimen thickness B. According to a large number of existing similar data, the corresponding relationship between the pre - crack length △a, the mean value (f1 + f2) / 2 of the pre - crack lengths on the two surfaces of the specimen, and the specimen thickness B is fitted as follows.
[0124] △a=(f 1 +f 2) / 2 + 0.0466B
[0125] According to the above formula, only by measuring the specimen thickness B and the crack propagation lengths f1 and f2 on the specimen surface can the pre-crack length be estimated more accurately, so that it can be applied to the rapid evaluation of the pre-crack length during the test process.
[0126] In a specific embodiment, in the four stages, the preset pre-crack lengths are as follows:
[0127] In the first stage, the sum of the initial crack length and the preset pre-crack length is 10.7 - 11.6 mm;
[0128] In the second stage, the sum of the initial crack length and the preset pre-crack length is 11.6 - 12.1 mm;
[0129] In the third stage, the sum of the initial crack length and the preset pre-crack length is 12.1 - 12.4 mm;
[0130] In the fourth stage, the sum of the initial crack length and the preset pre-crack length is 12.4 - 12.7 mm.
[0131] In the four stages, apply the corresponding load in each stage in sequence, and then measure the pre-crack length. When the length reaches the length preset for each stage, the load can be applied in the next stage.
[0132] In a specific embodiment, the preset crack propagation length △a of the pre-crack should be greater than 1.3 mm. The pre-crack lengths on the front and back surfaces of the specimen need to be between 1.5 mm and 1.7 mm, and the difference in pre-crack lengths between the two surfaces is not greater than 0.1 mm.
[0133] In a specific embodiment, when the pre-cracks in the 4 stages are all completed, remove the specimen, place it under a tool microscope for final pre-crack length measurement and image acquisition to determine the final pre-crack quality.
[0134] In a specific embodiment, the CT specimen is a 0.5T-CT specimen of low alloy ferritic steel.
[0135] Example
[0136] The embodiment of the present invention provides a method for making a pre-crack of a CT specimen of low alloy ferritic steel, which is made by the pull-pull fatigue method, and includes the following steps:
[0137] (1) First, according to the basic information such as the size of the specimen and the mechanical properties of the raw material, and in accordance with the requirements of the stress intensity factor envelope line in the ASTM E1921 Standard Test Method for Determination of Reference Temperature, To, for Ferritic Steels in the Transition Range standard (as shown in Figure 1 ), calculate the allowable load for pre-crack fabrication and design the pre-crack load levels for four stages;
[0138] (2) Before the test, draw multiple parallel lines with specific spacings at specific positions on both the front and back sides of the specimen. After the specimen is prepared, install the specimen at the test position of the material mechanics testing machine;
[0139] (3) Arrange 2 image acquisition cameras, arrange the light source, focus the cameras on the crack front positions on both the front and back sides of the specimen, obtain images through the monitor, and intercept and save the images through the computer;
[0140] (4) Using the tension-tension fatigue method, fabricate pre-cracks according to four preset and gradually decreasing constant loads. During the process, observe, measure, and record the crack propagation length in-situ and online. After reaching the preset pre-crack length, switch the load level;
[0141] (5) After the pre-cracks in the four stages are completed, remove the specimen and place it under a tool microscope for pre-crack length measurement and image acquisition.
[0142] The range of a for each stage 0 (a 0 is the sum of the length of the mechanical machining notch of the specimen and the length of the pre-crack), the corresponding load and stress intensity factor are shown in Table 2, the pre-crack load is shown in Figure 2 , and the stress intensity factor diagram is shown in Figure 3 .
[0143] Table 2 Pre-crack fabrication process method for 0.5T-CT specimens of RPV materials
[0144]
[0145]
[0146] It should be noted that the a 0 range, load, and K values in Table 2 are typical relatively conservative values, but may still vary slightly due to changes in the basic properties of the material.
[0147] The specific embodiments described above further elaborate on the purpose, technical solutions, and beneficial effects of the present invention. It should be understood that the above description is only for the specific embodiments of the present invention and is not used to limit the protection scope of the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.
Claims
1. A method for preparing a pre-crack of a low alloy ferrite steel CT specimen, using a tension-tension fatigue method, characterized in that: The steps include: S1, calculate the allowable load for pre-crack production based on the stress intensity factor requirements during fatigue; S2, draw lines at the designed positions on the front and back sides of the CT specimen; S3, installing the CT specimen into the test position of the testing machine; S4, performing pre-crack production by using a tension-tension fatigue method according to a preset load, and obtaining a pre-crack extension length until a preset pre-crack length is reached.
2. The method for making a pre-crack of a low alloy ferrite steel CT specimen according to claim 1, characterized in that: In the step S1, the allowable load includes four stages, the loads of the four stages decrease step by step and the load in each stage is constant.
3. The method for making a pre-crack of a low alloy ferrite steel CT specimen according to claim 2, characterized in that: The load ranges for the four stages are as follows: In the first stage, the load range is 4.8 to 5.2 kN; In the second stage, the load range is 3.8 to 4.2 kN; In the third stage, the load range is 3.4 to 3.6 kN; In the fourth stage, the load range is 2.8 to 3.2 kN.
4. The method for making a pre-crack of a low alloy ferrite steel CT specimen according to claim 3, characterized in that: The relationship between stress intensity factor K and load P is as follows: Where B is the sample thickness and W is the sample width; In the first stage, a0 represents the initial crack length, that is, the length of the notch pre-machined on the specimen before the fatigue test begins; In the second stage, a0 represents the sum of the initial crack length and the pre-crack length after expansion in the first stage; In the third stage, a0 represents the sum of the initial crack length and the pre-crack length after the second stage expansion; In the fourth stage, a0 represents the sum of the initial crack length and the pre-crack length after expansion in the third stage.
5. The method for making a pre-crack of a low alloy ferrite steel CT specimen according to claim 3, characterized in that: The stress intensity factor ranges of the four stages are as follows: In the first stage, the stress intensity factor range is 19~22MPam 0.5 ; In the second stage, the stress intensity factor range is 18-19 MPam 0.5 ; The third stage, the stress intensity factor range is 14 ~ 15MPam 0.5 ; The fourth stage, the stress intensity factor range is 13 ~ 14MPam 0.5 .
6. The method for making a pre-crack of a low alloy ferrite steel CT specimen according to claim 1, characterized in that: In step S4, the method for measuring the pre-crack extension length is as follows: Along the thickness B direction of the specimen, read the lengths a'1 and a'9 at 0.01B from the upper and lower surfaces of the specimen respectively, and take the lengths a'2, a'3, a'4, a'5, a'6, a'7, and a'8 at equal intervals of 0.01B between the upper and lower surfaces of the specimen to calculate the pre-crack length Δa:
7. The method for making a pre-crack of a low alloy ferrite steel CT specimen according to claim 1, characterized in that: In step S4, the method for measuring the pre-crack extension length is as follows: △a=(f1+f2) / 2+0.0466B Where f1 and f2 are the pre-crack lengths of the upper and lower surfaces of the specimen, respectively.
8. The method for making a pre-crack of a low alloy ferrite steel CT specimen according to claim 2, characterized in that: In the four stages, the preset pre-crack lengths in each stage are as follows: In the first stage, the sum of the initial crack length and the preset pre-crack length is 10.7-11.6 mm; In the second stage, the sum of the initial crack length and the preset pre-crack length is 11.6-12.1 mm; In the third stage, the sum of the initial crack length and the preset pre-crack length is 12.1-12.4 mm; In the fourth stage, the sum of the initial crack length and the preset pre-crack length is 12.4-12.7 mm.
9. The method for making a pre-crack of a low alloy ferrite steel CT specimen according to claim 7, characterized in that: In step S4, an image acquisition camera is used to observe, measure and record the crack extension lengths on the upper and lower surfaces of the sample in situ.
10. The method for making a pre-crack of a low alloy ferrite steel CT specimen according to claim 1, characterized in that: The CT sample is a low alloy ferrite steel 0.5T-CT sample.
